A NEW LIGHTWEIGHT CONCRETE SINGLE LEAF MASONRY WALLS SYSTEM DEVELOPMENT APPROACH - Sousa, L.C. (2011)
In this paper an approach to an optimized process to develop a single leaf lightweight concrete unit, made with expanded clay (LECA (R)) for external walls is presented. This research attempts to reconcile different aspects which are normally contradictory by using 2d and 3d finite elements analysis methods for both thermal requirements and for mechanical optimization. The resulting lightweight concrete unit is presented together with the associated masonry system. Finally the more important properties of the blocks and of the walls constructed from them are also presented